(untitled) (Research, Society and Development, 2019)
The Teaching of Sciences (TS) in Basic Education (BE) contributes with a vision of literacy necessary for the student to appropriate on a world reading in relation to Biology, Chemistry and Environmental Education. Specialist teachers can play an important role in the school routine when there is a collaborative work with the Classroom Teacher (CT). The present article has the objective of presenting a content alignment work carried out in the third year of BE with computer support. An action research carried out in a private school in the City of São Paulo showed that the students presented difficulties of retention of the knowledge of the TS made by CT. It so often happens that they do not have complete mastery over the contents that have to work in science and the support of the experts is welcome. A work of action research was done in which the support of the computer teacher occurred in relation to the content worked by the teacher regent. The study contributes to science teaching by showing computer science can provide a valuable learning aid when there is content alignment. Parallel work proved to be very effective in forming previous organizers for learning. The students were successful in evaluating